Happy Chickens Lay Tastier Eggs: Motivations for Buying Free-range Eggs in Australia. (3rd April 2017) - Bray, Heather J.; Ankeny, Rachel A.
ABSTRACT: Recent public interest in so-called "ethical" food production, and in particular the welfare of intensively housed farm animals, has been linked to an increase in sales of free-range eggs in several countries including Australia. Animal activist groups around the world have campaigned for the abolition of caged-egg production, retailers and large food companies are now sourcing less of these products, and governments in various locales have placed restrictions on caged-egg production. In addition, the recent focus on food production and preparation in popular culture including books, films, and television has made these practices, including those associated with eggs, more transparent to mainstream audiences. Previous studies have examined consumers' willingness-to-pay for free-range eggs, and community attitudes to animal welfare, but there has been little qualitative work that unpacks a key assumption which underlies much discussion of these issues: that free-range egg purchases are primarily or solely linked to consumers' desires to have egg production systems changed from intensive to free-range. This paper analyses qualitative research undertaken in Australia that explores consumers' motivations for buying free-range (or cage-free) eggs, which was part of a larger study examining ethical foods. Qualitative analysis of focus groups and interviews involving 73 participants revealed that free-range and cage-free eggs are perceived as being better quality, more nutritious, and safer, and having better sensory characteristics, than caged eggs. In response to open-ended questions, free-range and cage-free eggs were mentioned much more frequently than free-range meats, and were described as easy to identify and affordable, compared with other products with humane production claims. Several participants even had begun keeping their own hens in order to have an alternative to purchasing caged (or expensive free-range) eggs. Although caged-egg production was described by many participants as cruel, the desire to purchase free-range eggs was more often described in connection to efforts to avoid "industrialized" food than in relation to taking a stance on the issue of caged-hen welfare.